THE EFFECT OF KATUK LEAF GEL EXTRACT AS AN ANTI-INFLAMMATORY ORTHODONTIC TREATMENT ON CARRAGEENAN-INDUCED PAW EDEMA IN RATS - Hillda Herawati; Marlin Himawati; Diffa Nisa Nurfadillah (Journal of Health and Dental Sciences, 2023)
Katuk leaf herbal plants can be used as an anti-inflammatory drug because these contain flavonoids which be able to reduce inflammation by inhibiting cyclooxygenase enzyme formation. Katuk leaf extract is made in gel form at a 78.3 mg/kg BW dose. The gel is one of the medicinal preparations with good dispersion and longer adherence ability compared to ointments and creams. The study aimed to determine the effect of Katuk leaf extract gel as an anti-inflammatory orthodontic treatment against carrageenan-induced rat leg edema. This type of laboratory experimental research used a posttest-only control group design. This study used Katuk leaf extract gel in the treatment group and base gel for the control group, which was repeated 16 times in Wistar rat test animals in each group. The Independent variable is gel leaf Katuk extract, and volume-bound swelling on the soles of rats' feet is the dependent variable—univariate and bivariate data analysis with the Mann-Whitney test. The study showed no significant difference in the average edema between the control and treatment groups; Katuk leaf extract gel had no effect on an edema volume (p-value=0.12) compared to the control group. The conclusion is that Katuk leaf extract gel does not reduce swollen volume compared to Na-CMC 0.5%. DOI : 10.54052/jhds.v3n2.p135-146